Cross-categorial donkeys - Charlow, Simon (Proceedings of the Amsterdam Colloquium, 2011)
Data from surprising sloppy readings of verb phrase ellipsis constructions argue that ellipsis sites can partially or totally consist of dynamically bound pronouns. I give an account, integrating Muskens’ [11] CDRT with a focus-based theory of ellipsis and deaccenting (Rooth [14, 15]). The result is essentially a hybrid of Hardt [6] and Schwarz [19] but manages greater empirical coverage than either.